PENGGUNAAN METODE SPACED REPETITION DALAM PENINGKATAN KETERAMPILAN MENULIS KARAKTER BAHASA MANDARIN - Hasmawati, Hasmawati -; Krisnawati, Krisnawati; Noni, Nur Nasharuddin (Jurnal Bahasa Lingua Scientia, 2025)
This study aims to obtain data on the improvement of Mandarin character writing skills of students using the spaced repetition method. The subjects of this study were 29 students from the 5th grade at Zion Elementary School GKKA-UP Makassar. This research is a classroom action study consisting of two cycles. The data in this study are of two types: qualitative and quantitative. Qualitative data were obtained through observation, while quantitative data were obtained from writing skill tests in Cycle I and Cycle II. The results of the study showed that students' Mandarin character writing skills had an average score of 75 in Cycle I, categorized as fair, and improved in Cycle II with an average score of 85, categorized as good. These results indicate that the application of the spaced repetition method can improve the Mandarin character writing skills of 5th grade students at Zion Elementary School GKKA-UP Makassar.